Galectin-9 Is a High Affinity IgE-binding Lectin with Anti-allergic Effect by Blocking IgE-Antigen Complex Formation - Niki, Toshiro (American Society for Biochemistry and Molecular Biology, 2009)
Galectin (Gal)-9 was first described as an eosinophil chemoattractant. With the progress in research, Gal-9 has come to be known as a versatile immunomodulator that is involved in various aspects of immune regulations, and the entire picture of the function still remains elusive. To uncover as-yet unknown activity of Gal-9, we have been examining the effect of the protein in various disease animal models. Here we show that Gal-9 attenuated asthmatic reaction in guinea pigs and suppressed passive-cutaneous anaphylaxis in mice. These results indicate the mast cell stabilizing effect of Gal-9. In vitro studies of mast cell degranulation involving RBL-2H3 cells demonstrated that Gal-9 suppressed degranulation from the cells stimulated by IgE plus antigen and that the inhibitory effect was completely abrogated in the presence of lactose, indicating lectin activity of Gal-9 is critical. We found that Gal-9 strongly and specifically bound IgE, which is a heavily glycosylated immunoglobulin, and that the interaction prevented IgE-antigen complex formation, clarifying the mode of action of the anti-degranulation effect. Gal-9 is expressed by several mast cells including mouse mast cell line MC/9. The fact that immunological stimuli of MC/9 cells augmented Gal-9 secretion from the cells implies that Gal-9 is an autocrine regulator of mast cell function to suppress excessive degranulation. Collectively, these findings shed light on a novel function of Gal-9 in mast cells and suggest a beneficial utility of Gal-9 for the treatment of allergic disorders including asthma.